Hubungan Gaya belajar, Motivasi, dan Penyesuian diri Hasil Prestasi Belajar Mahasiswa Kedokteran - Silaban, Elfrida Megawaty; RVO, Ivonne; Syahrir, Lesmana (Jurnal Kedokteran Methodist, 2022)
Background: Education Faculty of Medicine in Indonesia has the aim of educating students with a learning process to complete their education. To see the success of learning from students, it is seen from the cumulative achievement index (GPA) which is a reflection of the results achieved from learning from the beginning of the semester to the end. Factors that can affect learning outcomes are learning styles, motivation and self-adjustment. Objective: To determine the relationship between learning styles, motivation, and self-adjustment to the learning achievement of medical students at HKBP Nommensen University. Method : This research is a quantitative research that uses a cross sectional. The number of samples is 62 respondents. Sampling was done by purposive sampling. The research was conducted at the Faculty of Medicine HKBP Nommensen Stambuk 2018 using the google form. Data presentation includes univariate and bivariate analysis using Pearson Correlation. Result : The results of bivariate analysis showed that there was a positive relationship between learning style and learning achievement (p-value= 0.006), there was a positive relationship between motivation and learning achievement (p-value <0.05), and there was a positive relationship between self-adjustment to learning achievement outcomes (p-value <0.05). Conclusion: Based on this research, it can be concluded that the variables of learning style, motivation, and self-adjustment have a significant and positive relationship to the learning achievement of medical students at HKBP Nommensen Stambuk 2018.